1999
DOI: 10.1034/j.1399-0039.1999.540511.x
|View full text |Cite
|
Sign up to set email alerts
|

DQB1*0602 confers genetic susceptibility to multiple sclerosis in Afro‐Brazilians

Abstract: We studied the distribution of the HLA-DRB1, -DQA1 and -DQB1 alleles in 44 Afro-Brazilian patients with multiple sclerosis and 88 controls. Although no significant differences were found between the patients and controls for the DRB1 and DQA1 alleles, the HLA-DQB1*0602 allele was positively associated with multiple sclerosis (45.0% vs. 17.0%, Pc=0.024, RR=3.31). The positive extended haplotypes for DQB1*0602 were more frequent in patients than controls, although the differences were not statistically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
2
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 17 publications
3
35
2
6
Order By: Relevance
“…Unlike previous studies conducted on Brazilian populations 8,24 , we did not observe an association between the HLA-DQA1*02:01-03:01 alleles and MS (Table 3). In addition, an association between HLA-DQB1*06:02 and MS in the absence of DRB1*15:01 was not observed in patients of African descent, which also does not agree with previous studies 10 . These inconsistent results may be due to differences in the ethnic admixtures of the analyzed population samples.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Unlike previous studies conducted on Brazilian populations 8,24 , we did not observe an association between the HLA-DQA1*02:01-03:01 alleles and MS (Table 3). In addition, an association between HLA-DQB1*06:02 and MS in the absence of DRB1*15:01 was not observed in patients of African descent, which also does not agree with previous studies 10 . These inconsistent results may be due to differences in the ethnic admixtures of the analyzed population samples.…”
Section: Discussioncontrasting
confidence: 93%
“…The fact that such a phenomenon is observed in Brazil could be attributed to the degree of ethnic admixing among the local population 10 . In a recent genome-screening survey, several novel loci were identified that showed significant associations with MS outcome, including IL2RA, IL7RA, CLEC16A, CD58, TNFRSFA1 and IRF8 27 , the majority of which are located near genes with immune functions or that have been associated with other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found significantly association of HLA DQB1*0602, HLA DRB1*1501 and DRB1*1503 alleles with ADEM monophasic patients. The HLA DQB1*0602 allele confers genetic susceptibility to Brazilian MS patients from Rio de Janeiro City (RJC), independently of the genetic background [21][22][23] . The presence of a common allele conferring genetic susceptibility for both MS and ADEM in the same population was found by Idrissovaet al 20 among Russian MS and ADEM patients.…”
Section: Discussionmentioning
confidence: 99%
“…A linkage genetic study in children showed that ADEM was associated with HLA DRB1*01 and DRB1*017(03) in the Russian population, and these alleles are associated with MS in Russian patients 20 . In Brazil, MS has been associated with HLA DR2 in Caucasian 21 patients and with HLA DQB1*0602 independently of DRB1*1501, in African-descendent patients of Rio de Janeiro City (RJC) [21][22][23] .…”
mentioning
confidence: 99%